Reliability and validity of the Thai version of the Pittsburgh Sleep Quality Index - Tullaya Sitasuwan (2018)
Objective: To assess the internal consistency, test-retest reliability, and validity of the Thai version of the Pittsburgh Sleep Quality Index (Thai-PSQI), which was recently translated using a standardized method, in Thai patients with major sleep disorders. Material and Method: The Thai-PSQI was developed under a standard translation protocol and administered to "bad" sleepers (i.e. patients with suspected obstructive sleep apnea [OSA], depression, or insomnia) and "good" sleepers in an academic tertiary care setting. All participants were asked to complete the same questionnaire after 2-4 weeks. Results: A total of 138 participants consisting of 69 patients with OSA, 28 with major depression, 11 with primary insomnia, and 30 controls completed the questionnaire. The global scores of the Thai-PSQI revealed that it had excellent internal consistency (Cronbach's alpha = 0.837) and test-retest reliability (intraclass correlation coefficient = 0.89). An analysis of covariance demonstrated a significant difference in Thai-PSQI global score between good sleepers and bad sleepers (p<0.001). A cut-off point of 5 out of 6 on the global score resulted in a sensitivity of 77.78% and specificity of 93.33%. Conclusion: The Thai-PSQI is a valid and reliable tool for screening and identifying the presence of significant sleep disturbances, and is comparable to the original English version.